2016
DOI: 10.1002/admi.201600172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Stable Solid Electrolyte Interphase Formation and Improved Cycling Stability of Tin‐Based Battery Anode in Fluoroethylene Carbonate‐Containing Electrolyte

Abstract: that enable to form a stable solid electrolyte interphase (SEI) layer at the surface of the alternative anode for reliable battery performance. Tin (Sn)-based anode material based on alloy formation with Li has been one of the promising candidates because of the large theoretical capacity (≈992 mAhg −1 ) of Sn compared to that of graphite (372 mAhg −1 ). Sn also holds its merits of appropriate operating voltage above Li, which prevents dendrite formation, and high electronic conductivity as metallic, and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The pattern obtained after 60 cycles ( C 60), which was ended as charged, is the same to those of charged anodes ( C 1, C 2, C 3). Slightly weakened peak intensity of recovered Mg 2 Sn phase upon charge, compared to pristine, might originate from a decrease in crystallinity or structural ordering by the possible occurrence of particle cracking event of this microsized Mg 2 Sn particles due to volume change, as often observed in the Sn‐based anodes in Li‐ion batteries . The peak of graphite is present at all states, confirming the role of graphite of being an electrochemically inactive but conductive agent.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The pattern obtained after 60 cycles ( C 60), which was ended as charged, is the same to those of charged anodes ( C 1, C 2, C 3). Slightly weakened peak intensity of recovered Mg 2 Sn phase upon charge, compared to pristine, might originate from a decrease in crystallinity or structural ordering by the possible occurrence of particle cracking event of this microsized Mg 2 Sn particles due to volume change, as often observed in the Sn‐based anodes in Li‐ion batteries . The peak of graphite is present at all states, confirming the role of graphite of being an electrochemically inactive but conductive agent.…”
Section: Resultsmentioning
confidence: 60%
“…Curve fitting was conducted on the broad Sn 3d 5/2 peaks ( Figure a) at 490–480 eV and Mg 2p peaks at 54–47 eV to determine the relative concentrations of various surface Sn and Mg species, whose fitting results are summarized in Figure a′ and Figure b′, respectively. First, the Sn 3d 5/2 spectrum of pristine anode (Figure a) exhibits that its surface consists of 38.2% Mg 2 Sn, as confirmed by the Mg 2p spectrum (Figure b), 16% Sn, 10.7% SnO, and 35.1% SnO 2 , as supported by O 1s spectrum ( Figure a) . The presence of surface Sn metal at pristine anode is likely associated with the trace of unreacted Sn during Mg 2 Sn synthesis, probably as remained at the surface, since it was not detectable in the powder XRD pattern (Figure ) that is a bulk analysis tool with the detection depth of ≈5 µm from the surface.…”
Section: Resultsmentioning
confidence: 80%
“…FEC, an electrolyte additive, is identified to boost up the performance of the anode materials, by stabilizing the SEI layer 58–60 . The presence of fluorinated carbonates (FEC) in the EC/DMC electrolyte solutions, escalate the first Coulombic efficiencies on FMGP due to the fast formation of SEI film.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fluorinated carbonates (FEC) in the EC/DMC electrolyte solutions, escalate the first Coulombic efficiencies on FMGP due to the fast formation of SEI film. A small addition of FEC additive is sufficient for the effective film formation on the graphite surface, it has also been investigated to improve SEI uniformity and eliminate Li dendrite formation on electrodes 60–65 . It was reported recently that addition of FEC additive in EC/DMC solvent produce SEI with completely different composition, compared to pure EC/DMC and found that the formed SEI layer is less current consuming and thus lower the loss of initial active lithium 62–67 …”
Section: Resultsmentioning
confidence: 99%
“…In Sony's patent, they tried different combinations of the electrolytes, showing that if the solvent contained FEC, the cycle characteristics were improved and the FEC content could be in a large range from 1 to 80 wt% [59]. A stable FEC-derived SEI layer may be the reason for improved cycling stability, while continuous electrolyte decomposition and variation in the composition and concentration of the SEI species are observed in EC-based electrolytes in Sn-based electrodes [60].…”
Section: Choice Of Electrolytementioning
confidence: 99%